Germline PALB2 Mutations in Cancers and Its Distinction From Somatic PALB2 Mutations in Breast Cancers - Hu, Zhe-Yu; Liu, Liping; Xie, Ning; Lu, Jun; Liu, Zhentian; Tang, Yu; Wang, Yikai; Yang, Jianbo; Ouyang, Quchang (Frontiers in Genetics, 2020)
PALB2 is an important BRCAx candidate for familial breast cancers (FBC). PALB2 pathogenic variants (PVs) may not to conform to “two hit” paradigm. However, a recent study demonstrates that in the majority PALB2 germline mutant breast cancers, the loss of heterozygosity (LOH) and somatic point mutations are the “second hit”. This study aimed to investigate the second hits in germline PALB2 mutations in breast cancers. We screened out 28 germline PALB2-mutation carriers among 480 familial cancer patients (including 143 FBC patients) in Geneplus database pool. Of the 143 patients with FBC, 10 had mono-allelic PALB2 germline mutations. All these germline PALB2 mutations were high-risk stop-gain, frameshift, or splicing mutations that concentrated in EX5–EX9 and might led to truncated proteins, severe functional defects and malignant phenotype. The hotspots were c.1057A[3>2] and c.3114-1G>A. Other mutations included c.389delA, c.2068C>T, c.2167_2168delAT, c.2629delT and c.2968G>T. Only one FBC patient has PALB2 somatic mutation and two patients had LOH of PALB2. All germline PALB2 mutations were high-risk mutations, whereas the somatic PALB2 mutations were moderate-risk missense mutations. We also distinguished PALB2 “novel mutations” from “reported mutations”. In conclusion, germline PALB2 mutation should be put into the context of future screening.